The relationship between perceived stress, spiritual well-being and alexithymia in people with epilepsy: A path analysis - Safiye, Yanmis; Gulcan, Bahcecioglu Turan; Zulfunaz, Ozer; Ersoy, Alevtina (Elsevier, 2024)
Aim: The present study was performed to investigate the associations among perceived stress, spiritual wellbeing, and alexithymia in people with epilepsy. Method: The study was performed with 140 patients diagnosed with epilepsy in the neurology clinic of a training and research hospital between May and December 2022. Personal Information Form, Perceived Stress Scale (PSS14), Spiritual Well-Being Scale (FACIT Sp-12), and Toronto Alexithymia Scale (TAS-20) were used to collect the data. Descriptive statistical methods, simple and multiple regression analyses, and path analysis were used to analyze the data. Results: The mean scores of the patients were 25.51 +/- 9.42 for PSS-14, 29.77 +/- 8.33 for FACIT Sp-12, and 56.55 +/- 16.87 for TAS-20. Concerning direct effects, a negative association was found between perceived stress and spiritual well-being, a positive association between perceived stress and alexithymia, and a negative association between spiritual well-being and alexithymia. The confirmed mediating effect was the role of spiritual well-being in the association between perceived stress and alexithymia. Perceived stress explained 28 % of spiritual wellbeing. In addition, the model explained 34 % of alexithymia in total. Conclusion: Perceived stress levels of people with epilepsy were low, while alexithymia and spiritual well-being levels were found to be moderate. It was found that as the stress levels perceived by people with epilepsy increased, alexithymia levels also increased. It was also found that the negative impact of perceived stress on alexithymia was reduced through spiritual well-being. The study shows how important spiritual well-being is in decreasing the negative impacts of perceived stress on alexithymia in people with epilepsy.
Keywords: Epilepsy; Stress; Spiritual well-being; Alexithymia; Nursing